Pengaruh Strategi Penjualan, Hubungan Dengan Pelanggan, Inovasi Produk, Adaptasi Teknologi Dan Dukungan Pemerintah Terhadap Kemampuan Bertahan Pedagang Di Pasar Tanjung Jember - Angga Pramudya Romadhon; Nely Supeni; Ahmad Sauqi (CV. ITTC INDONESIA, 2026)
The purpose of this study is to find out the influence of sales strategies, customer relations, product innovation, technological adaptation, and government support on traders' ability to survive.The population of this study is traders in the Tanjung Jember Market. The sample used was 60 respondents who were traders at the Tanjung Jember Market. The analysis method used multiple linear regression analysis. The tests used were data instrument tests (validity test and reliability test), classical assumption test (normality, multicolony, and heteroscedasticity test), multiple linear regression analysis, detrmination coefficient (R²), hypothesis test (t test and F test).The results show that some sales strategies have no significant effect on traders' ability to survive, some relationships with customers have no significant effect on traders' ability to survive, some product innovations have a significant effect on traders' ability to survive, some technological adaptations have no significant effect on traders' ability to survive, and some government support does not have a significant effect on traders' ability to survive. has a significant effect on the ability of traders to survive, and at the same time sales strategies, relationships with customers, product innovation, technological adaptation, and government support have a significant effect on the ability of traders to survive in the Tanjung Jember Market.